2015
DOI: 10.1037/rep0000027
|View full text |Cite
|
Sign up to set email alerts
|

Pain affects depression through anxiety, fatigue, and sleep in multiple sclerosis.

Abstract: Objective Over a quarter million individuals in the US have Multiple Sclerosis (MS). Chronic pain and depression are disproportionately high in this population. The purpose of this study was to examine the relationship between chronic pain and depression in MS and to examine potentially meditational effects of anxiety, fatigue and sleep. Methods Cross-sectional data from self-reported instruments measuring multiple symptoms and quality of life indicators were used in this study. Structural equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 68 publications
7
54
0
Order By: Relevance
“…Consistent with previous reports of patients with CP 32,39 and NCP, 1,34,47 the occurrence of moderate to severe pain was associated with a higher symptom burden. The severity of depression and anxiety differed among the pain groups.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous reports of patients with CP 32,39 and NCP, 1,34,47 the occurrence of moderate to severe pain was associated with a higher symptom burden. The severity of depression and anxiety differed among the pain groups.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, deterioration on the pain scale has not been reported in previous epidemiological or clinical studies using the RAND-36 or MSQOL-54 instruments [20][21][22][23] although the presence of chronic pain among PwMS has been noted [36][37]. Our study indicated deterioration in sexual activity on the 15D and the MSQOL-54 as well as in satisfaction with 9 sexual functioning on the MSQOL-54.…”
Section: Discussionsupporting
confidence: 48%
“…Depression shares a bidirectional relationship with insomnia, and may be exacerbated by the condition. [37] Chronic pain may also be exacerbated by insomnia in patients with MS, and a recent study suggests that poor sleep partially mediates the relationship between pain and depression in MS patients, making this an important component to consider in the treatment of depression [38]. A recent study using functional MRI also suggests an association between insomnia and subjective (though not objective) measures of cognitive function, as well as decreased thalamic functional connectivity [39].…”
Section: Insomniamentioning
confidence: 99%